Analysis of the integration pattern of waste management systems in local policies in Ambon city, Indonesia - Magrib, Novita Irma Diana; Lanuru, Mahatma; Lanuru, Mahatma; Demmalino, Eymal Bahsar (Edelweiss Applied Science and Technology, 2025)
Waste management remains a persistent challenge for urban areas in Indonesia, including Ambon City. This study aims to analyze the integration pattern of waste management systems as regulated through local policies, specifically the Regional Regulation (Perda) and Mayor Regulation (Perwali) in Ambon. A qualitative descriptive method was employed, using document analysis of relevant legal instruments, supported by semi-structured interviews with key stakeholders from the local government and waste management sector. The findings reveal a partial and fragmented integration between Perda and Perwali, particularly in institutional coordination, operational mechanisms, and community involvement. While both regulations address waste reduction and service improvement, inconsistencies in roles, responsibilities, and implementation procedures hinder effective integration. The novelty of this research lies in its focus on the alignment of multi-level local regulations as a strategic foundation for integrated urban waste governance. It highlights the need for harmonization between policy documents and practical execution to ensure regulatory coherence and efficiency. The study recommends revising existing policies to better define institutional roles, integrate technological support systems, and strengthen public participation frameworks. These measures are expected to enhance the sustainability and responsiveness of waste management in Ambon City.